2016
DOI: 10.15412/j.ptj.07050405
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Quality of Life Before and After Total Hip Arthroplasty Operation in Patients With Developmental Dysplasia of the Hip

Abstract: Purpose: Developmental dysplasia of the hip (DDH) increases the risk of secondary degenerative changes and subsequent total hip arthroplasty. The postoperative quality of life in patients with DDH who have been born and grown with this disability and adapted to it during the life, is one of the most challenging issues. This study aimed to compare the quality of life of patients with DDH before and after total hip arthroplasty (THA) operation. Methods:This research has a quasi-experimental/interventional design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…Although there was no difference between groups preoperatively, the THA group had substantial improvement in all SF-36 subsections postoperatively. Sanei et al [13] observed the highest improvement in the pain subsection, whereas we found the highest improvement was in the social role function closely followed by the mental health subsection. Cultural differences and social expectations may have contributed to this difference.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Although there was no difference between groups preoperatively, the THA group had substantial improvement in all SF-36 subsections postoperatively. Sanei et al [13] observed the highest improvement in the pain subsection, whereas we found the highest improvement was in the social role function closely followed by the mental health subsection. Cultural differences and social expectations may have contributed to this difference.…”
Section: Discussioncontrasting
confidence: 43%
“…Tellini et al [15] reported that QOL was improved in patients who underwent hip replacement for DDH. Likewise, a study by Sanei et al [13] showed that the mean SF-36 scores of patients with DDH increased from 27.41 to 79.12 points after THA, an immense improvement in QOL. In the present study, the increase in the scores of SF-36 subsections ranged from 22.0 to 58.64 points in patients who underwent THA.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several studies demonstrated long-term improvement in QoL after THA in patients diagnosed with DDH [88,89]. Although very important for patient, QoL assessment should be primarily used to identify their expectation regarding the type of treatment and should not replace clinical examination and standard diagnostic methods [90,91].…”
Section: The Follow-up Challenge: Hip Morphology Versus Functionmentioning
confidence: 99%
“…Many studies have shown that THA is effective at improving hip function (Sanei et al, 2016;Uhrbrand et al, 2014). However, in the case of balance ability, there have been conflicting reports depending on studies.…”
Section: ⅰ Introductionmentioning
confidence: 99%